HUBUNGAN ANTARA KOMITMEN DENGAN KEPUASAN PERNIKAHAN PADA DEWASA YANG MENJALANI PERNIKAHAN BEDA SUKU - Sesilia Widya Kristianti; Ratriana Yuliastuti Endang Kusumiati (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the relationship between marital commitment and marital satisfaction among young to middle-aged adults in interethnic marriages. The study involved 124 participants who had been married to partners of different ethnic backgrounds for at least two years and were aged between 25 and 60 years. This research used a quantitative correlational method with data collected through Likert-scale instruments, namely the Marital Components of Commitment (MCC) to measure marital commitment and the ENRICH Marital Satisfaction Scale (EMS) to measure marital satisfaction. Descriptive analysis showed that the mean score of marital commitment was 187.31 and marital satisfaction was 69.15, both categorized as moderate. The Pearson Product Moment correlation analysis resulted in r = 0.499 with a significance level of p = 0.000 (p < 0.05), indicating a significant positive relationship between marital commitment and marital satisfaction. This finding suggests that the higher the marital commitment, the higher the marital satisfaction experienced by individuals. The results imply the importance of fostering commitment to maintain stability and happiness in interethnic marriages